Level of screening for and vaccination against hepatitis B among healthcare workers in the Eastern Democratic Republic of the Congo: a public health concern - F.K. Sikakulya; D.K. Munyambalu; S.B. Mambo; A.K. Mutsunga; S.F. Djuma; P.A. Djuna; E. Ndiwelubula; W.A. Ngavo; S.M. Sahika; Patrick Kumbowi Kumbakulu; Kalima Nzanzu Adelard; T.A. Shindano (Elsevier, 2022)
Summary: Background: In low resource settings in sub-Saharan Africa healthcare workers (HCW) have a high risk of contracting hepatitis B infection. Vaccination of HCWs is to protect them from acquisition of hepatitis B from patients. Objective: To evaluate the hepatitis B virus (HBV) serological and vaccination status of HCWs in the Butembo Antenna in the Eastern Democratic Republic of Congo (DR Congo) and to investigate the factors influencing hepatitis screening and vaccination. Methods: A cross-sectional study using a structured questionnaire was carried out from 1st to 30th April 2021 among consenting HCWs in Butembo (≥18 years of age). Data was analysed using SPSS version 23. Results: Of 373 participants, 178 (47.7%) had already been screened for HBV. Screening was more likely for HCWs in a rural or publicly owned facility (P<0.05). A total of 25 (6.7%) HCWs were fully vaccinated against HBV; the factors associated with full vaccination were: prior screening for HBV (odds ratio: 9.03 (2.51-38.61), P<0.0001), prior knowledge of the value of post-exposure prophylaxis (odds ratio 12.9 (2.89-80.44), P=0.0004), prior knowledge of hepatitis B vaccine benefits (adjusted odds ratio: 4.54 (1.66-13.05), P=0.002) and prior exposure to hepatitis B infection (adjusted odds ratio: 2.61 (1.08-6.39), P=0.039). Conclusion: Screening and vaccination rates of HCWs for HBV are extremely low, and not high enough to prevent the spread of this serious illness and its complications. There is a dire need to increase vaccination rates among HCWs in Eastern DR Congo. The DRC government should issue vaccination against HBV as a recommendation at the national level.